Oral supplementation with fish oil reduces dryness and pruritus in the acetone-induced dry skin rat model. Issue 3 (September 2015) - Barcelos, Raquel C.S.; de Mello-Sampayo, Cristina; Antoniazzi, Caren T.D.; Segat, Hecson J.; Silva, Henrique; Veit, Juliana C.; Piccolo, Jaqueline; Emanuelli, Tatiana; Bürger, Marilise E.; Silva- Lima, Beatriz; Rodrigues, Luis M.
Highlights: Fish oil supplementation improves skin n -6/ n -3 ratio. Skin barrier dynamics seem to be positively influenced by skin n -6/ n -3 ratio decrease. Fish oil n -3 PUFA promotes skin protection against dry skin stimulus. Fish oil n -3 PUFA accelerates skin physiology recovery from dry skin stimulus. FO n -3 PUFA has suppressive effects on the scratching behaviour induced by dry skin. Abstract: Background: Pruritus and discomfort are often present in patients with xerosis and atopic dermatitis. Several studies suggest an important role of diet in skin pathophysiology. Objective: This study evaluated the effect of dietary fatty acids in the skin physiology via an itch-related animal model with and without supplementation with fish oil (FO), a source of polyunsaturated fatty acids (PUFA), especially omega 3 ( n -3). Methods: Male Wistar rats were divided into two groups—non-supplemented (control) and supplemented with FO (3 g/kg/day) by gavage for 90 days. Every 30 days, scratching and skin parameters (transepidermal water loss (TEWL), hydration, and local blood flow) were evaluated before and after dorsal skin exposure to acetone to induce the itch-related dry skin. At the end of the study, animals were sacrificed, and skin samples collected for fatty acids composition analysis by GC–FID. Results: FO supplementation reduced the TEWL and increased the skin hydration, with significant changes from day 60 on, while skin microcirculation registered no changes. It also alleviated the acetone induced skin barrier alteration, revealed by a faster resolution of TEWL and hydration, and elimination of itch-related scratching induced by dry skin. These changes were associated with the shift in the skin fatty acids incorporation pattern (richer in n -3 with n -6/ n -3 < 5) resulting from the FO supplementation. Conclusion: Skin barrier dynamics seem to be influenced by FO n -3 PUFA, with suppressive effects on the scratching behaviour induced by dry skin. Hence, long-term supplementation with n -3 PUFA rich nutrients might reinforce and restore cutaneous integrity and function.